2017
DOI: 10.5006/2558
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Duplex Stainless Steel in Industrial White Liquor

Abstract: Specimens of lean duplex and duplex stainless steel were exposed at 200°C in industrial white liquor from a Brazilian kraft mill using an autoclave to simulate the same conditions of digester processing. Tafel extrapolation method and weight loss were used to evaluate corrosion behavior of duplex steel in white liquor. The higher alloy steel, although presenting a lower corrosion rate than the lean duplex, presents a more severe selective attack on ferrite, at 200°C and 1.8 MPa, after Tafel extrapolation metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…although the corrosion of sulfur on steel in the alkaline solution has been studied by many scholars, most of them mainly focus on the corrosion of steel in white liquor, which contained the highest concentrations of alkaline and sulfur-contained species. esteves et al [7] studied the cyclic potentiodynamic polarization behavior of two steels in white and green liquors from a pulp processing plant. Feng, et al [8] evaluated the effect of temperature on the corrosion behavior of S32750 steel in white liquor.…”
Section: Introductionmentioning
confidence: 99%
“…although the corrosion of sulfur on steel in the alkaline solution has been studied by many scholars, most of them mainly focus on the corrosion of steel in white liquor, which contained the highest concentrations of alkaline and sulfur-contained species. esteves et al [7] studied the cyclic potentiodynamic polarization behavior of two steels in white and green liquors from a pulp processing plant. Feng, et al [8] evaluated the effect of temperature on the corrosion behavior of S32750 steel in white liquor.…”
Section: Introductionmentioning
confidence: 99%
“…Their study concluded that when DSS coupled with 316L stainless steel, the final substrate exhibit higher corrosion resistance (I corr = 560nA/cm 2 , CR = 0.006 mm/year). Esteves et al[47]…”
mentioning
confidence: 99%